The influence of endurance training on multiple sprint cycling performance - Glaister, M.; Stone, M. H.; Stewart, A. M.; Hughes, M. G.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2007)
The aims of the present study were to examine the effects of endurance training on multiple sprint cycling performance and to evaluate the influence of recovery duration on the magnitude of those effects. Twenty-one physically active male university students were randomly assigned to either an experimental (n = 12) or a control (n = 9) group. The experimental group cycled for 20 minutes each day, 3 times per week, for 6 weeks at 70% of the power output required to elicit maximal oxygen uptake (VO2max). Multiple sprint performance was assessed using 2 maximal (20 X 5 seconds) sprint cycling tests with contrasting recovery periods (10 or 30 seconds). All tests were conducted on a friction-braked cycle ergometer. Relative to controls, training resulted in a 0.2 L/min increase in mean VO2max (95% likely range: -0.04 to 0.44 L/min). Changes in anaerobic capacity (determined by maximal accumulated oxygen deficit) over the same period were trivial (p = 0.96). After training, the experimental group showed significant improvements (~40 W), relative to controls, in multiple sprint measures of peak and mean power output. In contrast, training-induced reductions in fatigue were trivial (p = 0.63), and there were no significant between-protocol differences in the magnitude of any effects. In summary, 6 weeks of endurance training resulted in substantial improvements in multiple sprint cycling performance, the magnitude of the improvements being largely unaffected by the duration of the intervening recovery periods.